Automation System for Single Photon Generation and Detection - Chan, Kar Tim (2009)
Single photon source can be produced by using spontaneous parametric down conversion or quantum emitter such as ions, molecules, atoms, quantum dots and colour centres. Main objective of current research is to automate single photon generation module and detection module based on nitrogen vacancy colour centre in diamond into one system. In single photon generation, diamond sample is held at a holder mounted on a 3D piezo translation stage. Laser source with wavelength 527nm is focused using a standard microscope objective to a spot size at the nitrogen vacancy centre to produce fluorescence. Since a single photon is generated by exciting an isolated nitrogen vacancy in a diamond crystal, it is critical that position of nitrogen vacancies in the crystal to be known. For this purpose, a scanning system was designed and constructed to determine the 3D position of nitrogen vacancy and identified their coordinates for later use. The system consists of a high precision 3D piezo translation stage and was controlled by a scanning programme built using LabVIEW. This programme will map the location of the vacancies in an intensity graph where axis X and Y show the scanning position while the bright colour spots determine the position of the vacancies. In single photon detection which is based on the Hanbury-Brown-Twiss setup, the fluorescence emitted from the nitrogen vacancy is split by a beamsplitter and directed to single photon detectors. A digital pulse is produced for each photocount detected. At the same time, output from the detectors is fed into a time to amplitude converter/single channel analyzer to produce coincidence counts. In order to read and record the number of photon counts and number of coincidences, a detection system was designed and built. This detection system interfaces a series of high performance single photon detectors to the same computer that controls the scanning system via a detection programme. Besides reading and recording data, the detection programme can also calculate the second order correlation function, g2(τ) from a subVI written in LabVIEW 8.2.